Particulate matter10-induced airway inflammation and fibrosis can be regulated by chitinase-1 suppression - Yong Jun Choi; Heejae Han; Jae-Hyun Lee; Jaeuk Lee; Chi Young Kim; Min Kwang Byun; Jae Hwa Cho; Hye Jung Park (Respiratory Research, 2023)
Abstract Background Particulate matter10 (PM10) can induce airway inflammation and fibrosis. Recently, chitinase-1 has been shown to play key roles in inflammation and fibrosis. We aimed to investigate the effects of chitinase-1 inhibitor in PM10-treated murine mice models. Methods In female BALB/c mice, PM10 was intranasally administered six times over 3 weeks, and ovalbumin (OVA) was intraperitoneally injected and then intranasally administered. Chitinase-1 inhibitor (CPX) 6 times over 3 weeks or dexamethasone 3 times in the last week were intraperitoneally administered. Two days after the last challenges, mice were euthanized. Messenger RNA sequencing using lung homogenates was conducted to evaluate signaling pathways. Results PM10 and/or OVA-induced airway inflammation and fibrosis murine models were established. CPX and dexamethasone ameliorated PM10 or PM10/OVA-induced airway hyper-responsiveness, airway inflammation, and fibrosis. CPX and dexamethasone also reduced levels of various inflammatory markers in lung homogenates. PM10 and OVA also induced changes in mRNA expression across an extreme range of genes. CPX and dexamethasone decreased levels of mRNA expression especially associated with inflammation and immune regulation. They also significantly regulated asthma and asthma-related pathways, including the JACK-STAT signaling pathway. Conclusions Chitinase-1 suppression by CPX can regulate PM10- and OVA-induced and aggravated airway inflammation and fibrosis via an asthma-related signaling pathway.